COMPLICATIONS OF ARTHROSCOPIC DRILLING IN THE TREATMENT OF OSTEOCHONDRITIS DISSECANS OF THE KNEE IN CHILDREN AND ADOLESCENTS. Issue 7 (30th July 2021) - Baghdadi, Soroush; Isaacs, David; Chan, Calvin; Wells, Lawrence; Ganley, Theodore J; Lawrence, John Todd
Background: Arthroscopic drilling is a well-established treatment for stable intact OCDs of the knee in children when non-operative treatment fails. The decision to proceed to operative treatment requires a discussion regarding the risks and benefits of surgical intervention. While there is abundant data suggesting that OCD drilling is a highly effective treatment strategy, there is little data specifically evaluating the risks and complications of this procedure. Purpose: The goal of this study was to assess the complications of drilling of stable OCDs of the knee, and the risk factors for developing complications. Methods: In a retrospective chart review from 2009-2017, data from patients <18 years old who underwent arthroscopic drilling for stable intact OCD lesions of knee were collected. Lesions treated with other techniques (fixation, chondroplasty, OATS), and those with <3 months of follow-up were excluded. Characteristics of the lesions, treatment approach, and post-operative course were recorded. For bilateral surgeries, each knee was considered a separate record. Results: 139 knees in 131 patients were evaluated, of which 102 (73%) were male. The mean age was 12.7years. 108 knees (77%) had an open physis at the time of operation. Patients were managed conservatively for a mean of 6.76 months pre-operatively (SD=6.6). Average follow-up was 14.8 months after the initial surgery (SD=13.25). 53 patients (38%) were obese or overweight at the time of surgery. All patients regained full ROM within 5° of the contralateral knee at a mean 12.9 weeks post-op (SD=3.2), with all but 7 (5 %) returning to activities of daily living at the 3-month visit. No cases of infection, stiffness, arthrofibrosis, or other procedure-related complications were recorded. 6 knees (4.3%) underwent 7 additional surgeries during the follow-up period, all of which were for treatment failure in non-healing lesions (loose body removals, chondroplasty, or repeat drilling). In a multiple logistic regression model, age, gender, status of the physis at the time of surgery, BMI percentile, and OCD size were not predictive of the need for additional surgeries. Discussion: Our findings suggest that arthroscopic drilling for OCDs of the knee is a safe procedure with minimal risk of complications. The majority of patients return to their pre-operative daily activity level with full ROM by 3 months after surgery. Complications, including reoperation, were related to the progression of the OCD, rather than the surgical procedure.